Reduction of Intraocular Pressure and Aqueous Outflow Resistance After Modified 360-degree Suture Trabeculotomy. Issue 3 (12th March 2023) - Suzuki, Kayo; Shinmei, Yasuhiro; Hirooka, Kiriko; Kanaya, Rina; Shinkai, Akihiro; Kijima, Riki; Chin, Shinki; Ito, Yoichi M.; Ishida, Susumu
Abstract : Précis: Decreasing aqueous outflow resistance at trabecular meshwork is the main mechanism of modified 360-degree suture trabeculotomy (ST), and the preoperative C-value, which shows aqueous outflow resistance, is likely to be useful for predicting intraocular pressure (IOP) reduction. Purpose: To clarify the mechanism of IOP reduction and the preoperative prognostic predictor of modified 360-degree ST. Materials and Methods: Forty-three eyes of 32 patients with glaucoma who underwent ST at Hokkaido University Hospital between April 2017 and February 2020 were enrolled. The records of postoperative IOP and coefficient of aqueous outflow (C-value) after ST were reviewed from clinical charts retrospectively. Preoperative IOP and C-values were also reviewed and considered as the baseline. Results: Although the differences were not significant, IOP decreased to 15.4±3.3 mm Hg at 3 months ( P =0.10) and 16.1±3.8 mm Hg at 6 months ( P =0.21). In addition, there were significant decreases in anti-glaucoma medication scores at both 3 and 6 months after surgery ( P <0.01). The C-value increased significantly to 0.24±0.11 µL/min/mm Hg at 3 months ( P <0.01) and increased significantly to 0.27±0.14 µL/min/mm Hg at 6 months ( P <0.01). The rates of change in IOP were negatively correlated with that in the C-value at 3 months ( r =−0.49 P <0.01) and 6 months ( r =−0.46 P <0.01). The success rate (IOP<21 mm Hg, IOP reduction>20%) was greater in the low baseline C-value group (≤0.17) than high baseline C-value group (>0.17) ( P <0.05), and the baseline IOP and C-values were statistically significant in association with the success ( P <0.05) at 6 months. Conclusions: Increased conventional outflow by the elimination of the aqueous outflow resistance at the trabecular meshwork is the main mechanism of IOP reduction after ST. Preoperative examination of tonographic outflow facility may be useful for predicting the IOP reduction and outcome of ST.